Behavioral Self-Regulation: A Comparison of Goals and Self-Monitoring for High School Students With Disabilities. (September 2022) - Estrapala, Sara; Bruhn, Allison Leigh; Rila, Ashley
High school students, particularly those with disabilities, often struggle with academic engagement in general education classes. One empirically supported method for improving academic engagement includes self-regulation interventions. However, individual effects of frequently used self-regulation strategies' goal setting and self-monitoring remain unknown. To address this issue, we implemented a multiple-probe single-case design with embedded alternating treatments to evaluate the differential impact of behavioral goal reminders and self-monitoring. The sample consisted of three high school students with emotional or behavioral disorders (EBD) in general education classes who also received special education services. Innovative approaches to intervention design included student-determined behavioral goals and self-monitoring procedures informed by triangulated behavioral assessment data. Although visual analysis indicated only moderate improvements in academic engagement, and no functional relationships were determined for either the multiple-probe or alternating treatments designs, the intervention was rated with high social validity from teachers and students, and the study represents an exemplar of high-quality special education single-case research. Practical implications, limitations, and directions for future research are discussed.